Relationship between lower extremity strength asymmetry and linear multidimensional running in female tennis players - Cenab Turkeri; Bariscan Oztürk; Murat Koç; Hakan Engin; Eren Uluöz; Cem Yoksuler Yılmaz; Banu Nurdan Özsu; Lutfi Tolga Celik; Mehmet Emin Şeker; İsmail Çiçek; Caner Uzunca; İbrahim Bahçivan; et al. (PeerJ, 2024)
Background Tennis requires movement abilities in changing playing situations. This article investigates the relationship between lower extremity strength asymmetry ratio and linear and multidimensional running performances in female tennis players. Methods A total of 56 female tennis players, with a mean age of 15.44 ± 0.50 years, participated in the study—the research design involved three sessions at 48-hour intervals. In the first session, athletes performed dominant and non-dominant countermovement jump (CMJ) and board jump (BJ) tests. The second (sec) session included 10-meter (−m) and 30-m linear running performance tests, while the final session assessed multidimensional running performance with a change of direction (COD) test. The relationship between CMJ and BJ asymmetry ratios and linear and multidimensional running performances was analysed using the Pearson correlation coefficient. Bilateral asymmetry rates in linear and multidimensional running performance were determined through linear regression analysis. Results The dominant CMJ recorded 17.56 ± 3.47 cm, while BJ was 130.23 ± 21.76 cm, and the non-dominant CMJ measured 16.79 ± 4.51 cm with a BJ of 147.52 ± 30.97 cm. The athletes had a CMJ asymmetry rate of 12.67 ± 11.29% and a BJ asymmetry rate of 7.19 ± 5.28%. A relationship was seen between the CMJ asymmetry rate and 30-m running performance (r = 0.368, p < 0.05). There was no correlation between BJ asymmetry rate and 10-m running performance. Significant correlations were found between 30-m (r = 0.364) and COD (r = 0.529) running performances (p < 0.05). Conclusions It can be said that the CMJ asymmetry ratio may negatively affect 30-m and the BJ asymmetry ratio may negatively affect 30-m and COD performance.